RISIKO INISIASI MENYUSU DINI DAN PRAKTEK ASI EKSKLUSIF TERHADAP KEJADIAN STUNTING PADA ANAK 6-24 BULAN (EARLY BREASTFEEDING INITIATION AND EXCLUSIVE BREASTFEEDING AS RISK FACTORS OF STUNTING CHILDREN 6-24 MONTHS-OLD) - M Rizal Permadi; Diffah Hanim; Kusnandar Kusnandar; Dono Indarto (Persagi, 2016)
ABSTRACTSome of causes of stunting are the deferment of early breastfeeding initiation and the administration of the non-exclusive breastfeeding. The objective of this study was to elaborate relationship of early breastfeeding initiation and exclusive breastfeeding administration history to the stunting. This sudy used the observational analytical research method with the cross-sectional design. Its subjects were 33 stunting and 77 non-stunting children aged 6-24 months in Boyolali Regency. Data was analyzed by using the chi-square test and multiple logistic regression analysis. The stunting children who got the early breastfeeding initiation were 14, and those who did not get the early breastfeeding initiation were 19. The stunting children who got the exclusive breastfeeding were 4 and those who did not get the exclusive breastfeeding were 29. Early breastfeeding initiation and exclusive breastfeeding had a significant correlation with the stunting as indicated by the p-value <0.05. The children who did not get the early breastfeeding initiation have the possibility of 3.69 times higher to suffer from stunting than those who got the early breastfeeding initiation. In addition, the children who did not get the exclusive breastfeeding have the possibility of 9.5 times higher to suffer from stunting than those who got the exclusive breastfeeding. Therefore, nutrition education to the gestational mothers on the importance of exclusive breastfeeding administration is required.ABSTRAK Penyebab masalah stunting antara lain akibat dari penundaan inisiasi menyusu dini (IMD), dan pemberian air susu ibu (ASI) tidak eksklusif. Penelitian ini bertujuan untuk menganalisis hubungan IMD dan ASI eksklusif dengan kejadian stunting. Penelitian observasional ini dilaksanakan di Boyolali dengan menggunakan pendekatan cross-sectional. Partisipan terdiri dari 33 anak stunting dan 77 anak tidak stunting berusia 6-24 bulan. Analisis data menggunakan uji chi-square dan regresi logistik berganda. Partisipan anak stunting yang mendapatkan IMD sebanyak 14 orang dan tidak mendapatkan IMD sebanyak 19 orang. Anak stunting yang mendapatkan ASI eksklusif sebanyak 4 orang dan yang tidak sebanyak 29 orang. Inisiasi menyusu dini dan ASI eksklusif memiliki hubungan yang bermakna dengan kejadian stunting (p<0,05). Anak yang tidak mendapatkan IMD memiliki kemungkinan 2,63 (1,02-6,82) kali lebih tinggi mengalami kejadian stunting, selain itu anak yang tidak mendapatkan ASI eksklusif memiliki risiko mengalami kejadian stunting 7,86 (2,43-25,4) kali lebih tinggi dibandingkan anak yang mendapatkan ASI eksklusif. Oleh karena itu, diperlukan edukasi gizi kepada ibu hamil mengenai pentingnya pemberian ASI eksklusif.